2014
DOI: 10.4103/2277-9175.124639
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adding topical simvastatin to topical calcipotriol on improvement of cutaneous plaque psoriasis

Abstract: Background:Psoriasis is a common dermatologic disorder, with fluctuating response to treatment. Considering the proven immunomodulatory effects of oral simvastatin in psoriasis, this trial study was enrolled to determine whether the topical form has also antipsoriatic effects. Vitamin D analogs known to be effective and are considered the first line of therapy in mild to moderate cases. In this study, the efficacy of topical calcipotriol 0.005% ointment (as a standard method of treatment for psoriasis) versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Another study evaluated the efficacy of adding topical simvastatin to topical calcipotriol in psoriasis. Even though the PASI scores kept going down in both groups, topical simvastatin wasn’t statistically better at treating psoriasis ( 66 ). Other studies have found that statins may worsen psoriasis lesions ( 67 , 68 ).…”
Section: Cholesterol Metabolism and Psoriatic Inflammationmentioning
confidence: 99%
“…Another study evaluated the efficacy of adding topical simvastatin to topical calcipotriol in psoriasis. Even though the PASI scores kept going down in both groups, topical simvastatin wasn’t statistically better at treating psoriasis ( 66 ). Other studies have found that statins may worsen psoriasis lesions ( 67 , 68 ).…”
Section: Cholesterol Metabolism and Psoriatic Inflammationmentioning
confidence: 99%